Singlet Oxygen Attack on Guanine: Reactivity and Structural Signature within the B‐DNA Helix. Issue 35 (21st July 2016) - Dumont, Elise; Grüber, Raymond; Bignon, Emmanuelle; Morell, Christophe; Aranda, Juan; Ravanat, Jean‐Luc; Tuñón, Iñaki
Abstract: Oxidatively generated DNA lesions are numerous and versatile, and have been the subject of intensive research since the discovery of 8‐oxoguanine in 1984. Even for this prototypical lesion, the precise mechanism of formation remains elusive due to the inherent difficulties in characterizing high‐energy intermediates. We have probed the stability of the guanine endoperoxide in B‐DNA as a key intermediate and determined a unique activation free energy of around 6 kcal mol −1 for the formation of the first C−O covalent bond upon the attack of singlet molecular oxygen ( 1 O2 ) on the central guanine of a solvated 13 base‐pair poly(dG‐dC), described by means of quantum mechanics/molecular mechanics (QM/MM) simulations. The B‐helix remains stable upon oxidation in spite of the bulky character of the guanine endoperoxide. Our modeling study has revealed the nature of the versatile 1 O2 attack in terms of free energy and shows a sensitivity to electrostatics and solvation as it involves a charge‐separated intermediate. Abstract : Guanine attack : Singlet oxygen attack on guanine in B‐DNA with the formation of guanine endoperoxide and its subsequent intramolecular cyclization have been investigated based on QM/MM‐MD simulations. The results revealed an easy stepwise mechanism and electrostatic embedding decisive to stabilizing a charge‐separated intermediate (see figure).